2020
DOI: 10.1152/ajprenal.00208.2019
|View full text |Cite
|
Sign up to set email alerts
|

Kidney dysfunction induced by a sucrose-rich diet in rat involves mitochondria ROS generation, cardiolipin changes, and the decline of autophagy protein markers

Abstract: The mechanistic link between obesity and renal failure has been proposed to involve mitochondria reactive oxygen species generation and lipotoxicity. These pathological conditions make mitochondria of particular interest in the regulation of cell function and death by both apoptosis and autophagy. Therefore, this work was undertaken to investigate mitochondria function, autophagy, and apoptosis protein markers in the kidney from a rat model of intra-abdominal obesity and renal damage induced by a high-sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…Consuming 30%g/vol fructose in drinking water for 5.5 months led to a 20% increase in body mass as a result of intra-abdominal fat expansion compared to chow-fed young rats [30]. Consuming 30%g/vol sucrose in drinking water also increased hydrogen peroxide generation and lipid peroxidation in the kidney [31]. Another study comparing the effects HFD and HSD (both 30%g/g or g/vol) found that despite both diets inducing similar weight gain (12%) and similar levels of hepatic fat content after 8-12 months, only HSD-induced hyperleptinemia and hyperinsulinemia in addition to increased lipogenic gene expression like sterol regulatory element-binding transcription factor 1 (SREBP1) and peroxisome proliferator-activated receptors gamma (PPARλ) increased nitrosylation of mitochondrial proteins, and increased expression proteins involved in mitochondrial fission like dynamin-related protein 1 relative to fusion protein mitofusin [32].…”
Section: Hallmark Of Agingmentioning
confidence: 92%
“…Consuming 30%g/vol fructose in drinking water for 5.5 months led to a 20% increase in body mass as a result of intra-abdominal fat expansion compared to chow-fed young rats [30]. Consuming 30%g/vol sucrose in drinking water also increased hydrogen peroxide generation and lipid peroxidation in the kidney [31]. Another study comparing the effects HFD and HSD (both 30%g/g or g/vol) found that despite both diets inducing similar weight gain (12%) and similar levels of hepatic fat content after 8-12 months, only HSD-induced hyperleptinemia and hyperinsulinemia in addition to increased lipogenic gene expression like sterol regulatory element-binding transcription factor 1 (SREBP1) and peroxisome proliferator-activated receptors gamma (PPARλ) increased nitrosylation of mitochondrial proteins, and increased expression proteins involved in mitochondrial fission like dynamin-related protein 1 relative to fusion protein mitofusin [32].…”
Section: Hallmark Of Agingmentioning
confidence: 92%
“…Previous research has shown that there is a link between mitochondrial dysfunction and kidney failure. [32][33][34] Kidney energy (adenosine triphosphate [ATP]) demand for normal functions is high.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, що дисфункція мітохондрій, що виникає внаслідок порушення регуляції роботи дихального ланцюга, зниження мембранного потенціалу, супроводжується зменшенням вмісту АТФ та інтенсифікацією генерації АФК, що сприяє пошкодженню нирок (Bhatia et al, 2020;Ruiz-Ramírez et al, 2020). У нормі в нирках біля 90 % АТФ, необхідної для реабсорбції глюкози, іонів та метаболітів, утворюється шляхом окисного фосфорилювання (Braga, et al, 2022), при цьому дисбаланс процесів енергоутворення в першу чергу буде супроводжуватися порушенням реабсорбційної та фільтраційної здатності нирок.…”
unclassified